Formation of beta-nickel hydroxide plate-like structures under mild conditions and their optical properties - de Moura, A. P. [UNESP]; Lima, R. C.; Paris, E. C.; Li, M. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Nanostructural beta-nickel hydroxide (beta-Ni(OH)(2)) plates were prepared using the microwave hydrothermal (MH) method at a low temperature and short reaction times. An ammonia solution was employed as the coordinating agent, which reacts with [Ni(H2O)(6)](2+) to control the growth of beta-Ni(OH)(2) nuclei. A trigonal beta-Ni(OH)(2) single phase was observed by X-ray diffraction (XRD) analyses, and the crystal cell was constructed with structural parameters and atomic coordinates obtained from Rietveld refinement. Field emission scanning electron microscopy (FE-SEM) images revealed that the samples consisted of hexagonal-shaped nanoplates with a different particle size distribution. Broad absorption bands assigned as transitions of Ni2+ in oxygen octahedral sites were revealed by UV-vis spectra. Photoluminescence (PL) properties observed with a maximum peak centered in the blue-green region were attributed to different defects, which were produced during the nucleation process. We present a growth process scheme of the beta-Ni(OH)(2) nanoplates. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: beta-Ni(OH)(2) nanoplates; Microwave-hydrothermal; Growth mechanism; Rietveld refinement; Photoluminescence property